Simplified CRB-65 for risk stratification and predicting prognosis in acute pulmonary embolism - Keller, K.; Coldewey, M.; Dippold, W.; Beule, J.; Balzer, J. O. (Phlebologie, 2015)
Background: Pulmonary embolism (PE) and community acquired pneumonia (CAP) are potentially life-threatening diseases. In CAP CRB-65 is used for risk stratification and prognosis prediction. The aim of this study was to examine a simplified CRB-65 (sCRB-65) for predicting prognosis in PE.Methods: We retrospectively analyzed the data of 182 PE patients. Patients were, according to the score of sCRB-65 (respectively 1 point for dyspnoea, systolic blood pressure < 90 mmHg or diastolic blood pressure60 mmHg, age65years), subdivided in risk-classes 1–4.Risk classes were compared with Kruskal-Wallis test. Logistic multivariable regression and Pearson correlation matrix were calculated for coherence of sCRB-65 and in-hospital death, right ventricular load and PE severity stadium as well as sCRB-65 > 2points and in-hospital death an PE stadium. ROC analysis was performed to evaluate efficiency of sCRB-65 score to predict in-hospital death and PE severity stadium.Results: PE severity stadium, systolic pulmonary artery pressure (sPAP) and frequency of in-hospital death increased with growing risk class.Risk class 1 showed lower PE sever-ity stadium than 2 (P=0.0253), 3 (P=0.0132) and 4 (P=0.00162), lower percentage of patients with sPAP > 30mmHg than 2 (0 % vs. 48.9 %, P=0.0419), 3 (0 % vs. 70.8 %, P=0.00112) and 4 (0 % vs. 75.0 %, P=0.0113). Frequency of in-hospital deaths was higher in risk class 4 than in 1 (P=0.0024), 2 (P=0.00014) and 3 (P=0.000058). Multi-variable logistic regression showed an association between sCRB-65 scored>0 and PE severity stadium (OR 11.42, 95 %CI: 1.35–96.66, P=0.0254), RVD (OR 10.09, 1.16–87.78, P=0.0363) and sPAP (OR 1.08, 1.02–1.15, P=0.0092) as well as a trend towards significance (OR 12.39, 0.90–171.34, P=0.060) between in-hospital death and sCRB-65. sCRB-65 correlated with PE severity stadium (r=0.258, P<0.001) and sPAP (r=0.280, P=0.001). sCRB-65 >2 points was strongly associated with both inhospital death (OR 36.22, 95%CI: 1.59–827.71, P=0.0245) and high-risk PE stadium (OR 57.94, 95%CI: 7.17–468.33, P=0.000141). ROC analysis for CRB-65 predicting in-hospital death and high-risk PE stadium showed AUC values of respectively 0.764 and 0.892 with sCRB-65 cut-off value of 2.5 points, respectively.Conclusions: sCRB-65 is closely correlated with PE severity stadium and load of the right heart as well as prognosis. PE patients with sCRB-65 score >2 points revealed a 36.2-fold risk to die during in-hospital course after acute PE event. Efficiency of sCRB-65 to predict in-hospital death was good.
Keywords: Pulmonary artery pressure; risk stratification; pulmonary embolism; right ventricular dysfunction; CRB-65; thrombosis